2020
DOI: 10.1086/706622
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Comprehensive Smoking Bans on the Health of Infants and Children

Abstract: As evidence of the negative effects of environmental tobacco smoke (ETS) has mounted, an increasingly popular public policy response has been to impose restrictions on smoking through 100% smoke-free bans (comprehensive smoking bans). Yet sparse information exists regarding the impact these smoking bans at the state and local levels have on the health of children and infants. A rationale for expansion of smoke-free laws implicitly presumes that potential public health gains from reducing adult cigarette consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…Early studies using birth records documented that higher cigarette taxes reduce smoking among pregnant women with implied own‐tax elasticities of ‐0.7 to ‐1.0 (Colman et al., 2003; Ringel & Evans, 2001). While not estimating a prenatal smoking tax elasticity directly, McGeary and colleagues (2019) found evidence consistent with prior literature of the effect of cigarette taxes on birth outcomes using birth certificate data through 2012. Other recent studies have suggested cigarette tax‐elasticities of demand for pregnant women are lower in recent years (Adams et al., 2012; Hoehn‐Velasco et al., in press).…”
Section: Background and Related Literaturesupporting
confidence: 70%
See 2 more Smart Citations
“…Early studies using birth records documented that higher cigarette taxes reduce smoking among pregnant women with implied own‐tax elasticities of ‐0.7 to ‐1.0 (Colman et al., 2003; Ringel & Evans, 2001). While not estimating a prenatal smoking tax elasticity directly, McGeary and colleagues (2019) found evidence consistent with prior literature of the effect of cigarette taxes on birth outcomes using birth certificate data through 2012. Other recent studies have suggested cigarette tax‐elasticities of demand for pregnant women are lower in recent years (Adams et al., 2012; Hoehn‐Velasco et al., in press).…”
Section: Background and Related Literaturesupporting
confidence: 70%
“…Infants born to women smoking in the 3 rd trimester were almost twice as likely to have experienced low birthweight, 48% more likely to have been born prematurely, and 1.5 times less likely to have survived their first year of life, compared to infants born to women who did not smoke during pregnancy. 1 Quasi-experimental evidence using policy variation in cigarette taxes supports descriptive evidence that smoking reduces birth weight (McGeary et al, 2019, Evans and Ringel, 1999, Lien and Evans, 2005, and increases risk for premature birth (McGeary et al, 2019) and infant mortality (Sen andPiérard, 2011, Markowitz, 2008).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…By 2012, over 48% of the population was exposed to a comprehensive worksite ban, over 64% were exposed to full bans in restaurants, and over 60% were exposed to these restrictions in freestanding bars. For a fuller description of the ban exposure see the online appendices and McGeary et al (2017).…”
Section: Tobacco Policymentioning
confidence: 99%
“…Anger, Kvasnicka, and Siedler () reported that, after the implementation of state‐level public smoking ban in bars, restaurants, and dance clubs in Germany, the prevalence of smoking among people who often go out to such places fell significantly. In the United States, comprehensive indoor smoking bans effectively reduced smoking rates (Carton, Darden, Levendis, Lee, & Ricket, ) and improved the health of infants and children (McGeary, Dave, Lipton, & Roeper, ).…”
Section: Introductionmentioning
confidence: 99%